ISSUES OF INFORMATION THREAT PREVENTION IN THE MILITARY AND POLITICAL SPHERE (Scientific journal of the Fergana State University, 2024)
The article examines the prevention of information threats in the military-political sphere. It is scientifically proven that the negative trends occurring in the information space cause serious problems in the political, economic, social and other spheres of the countries.